Efektivitas Pemberian Makanan Tambahan (PMT) Pemulihan Pada Status Gizi Balita di Wilayah Kerja Puskesmas Simomulyo, Surabaya - Arum Sekar Rahayuning Putri; Trias Mahmudiono (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2020)
Background: One of the efforts made in overcoming malnutrition in the toddler age group is by implementing a Recovery Supplementary Feeding program.Objectives: The purpose of this study was to analyze the differences in nutritional status of children based on weight for height before and after the Supplementary Food Recovery and differences in nutritional status of children after Supplementary Food Recovery and when they had not received Supplementary Food Recovery in the Simomulyo Community Health Center work area.Methods: This study was observational study using case-control design. A total of 38 toddlers with history of obtaining Supplemental Feeding Recovery (PMT) Program in the working area of Simomulyo Health Center were randomly selected. Nutritional status of toddlers is obtained using anthropometric methods of body weight and height / body length. Statistically tested using t-test paired with a significance level of <0.05.Results: After not getting Supplemental Feeding Recovery, it was found that 2.6% of children under five severely wasting, 34.2% wasting, and 63.2% had normal nutritional status. There was a decrease in the percentage of infants with normal nutritional status compared to after completing PMT Recovery program from 68.4% to 63.2%. There were no significant differences in nutritional status of children before and after the program (p=0.585). There was no difference between the nutritional status of children under five after the program and when they had not received the program (p=0.430)Conclusions: There was no difference in nutritional status of children (weight-for-height) before and after Supplemental Feeding Recovery Program.ABSTRAK Latar Belakang: Upaya yang dilakukan dalam mengatasi kekurangan gizi pada kelompok usia balita adalah program Pemberian Makanan Tambahan (PMT) Pemulihan.Tujuan: Penelitian ini dilakukan bertujuan untuk menganalisis adanya perbedaan pada status gizi balita berasarkan BB/TB sebelum dan setelah Pemberian Makanan Tambahan (PMT) Pemulihan serta perbedaan status gizi balita setelah PMT Pemulihan dan saat sudah tidak mendapat PMT Pemulihan di wilayah kerja Puskesmas Simomulyo.Metode: Penelitian ini adalah peneitian observasional dengan desain penelitan cross sectional. Lokasi penelitian adalah di wilayah kerja Puskemas Simomulyo, Surabaya. Sebanyak 38 balita dengan riwayat mendapat PMT Pemulihan dipilih secara acak menggunakan metode simple random sampling. Status gizi balita didapat menggunakan metode antropometri berat badan dan tinggi/panjang badan. Indeks BB/TB digunakan dalam penilaian status gizi dengan alasan sasaran utama PMT Pemulihan adalah balita dengan status gizi kurus. Uji secara statistik dilakukan menggunakan uji t berpasangan dengan tingkat signifikansi <0,05.Hasil: Setelah 3 bulan mendapat PMT Pemulihan ada peningkatan persentase balita dengan status gizi normal dari 65,8% menjadi 68,4%. Setelah tidak mendapat PMT Pemulihan ada penurunan persentase balita dengan status gizi normal menjadi 63,2%. Tidak ada perbedaan yang bermakna status gizi balita berasarkan BB/TB sebelum dan setelah PMT Pemulihan (p=0,585). Tidak ada perbedaan pada status gizi dapat disebabkan oleh konsumsi PMT yang belum optimal. Begitu juga diketahui tidak ada perbedaan yang bermakana status gizi balita setelah PMT Pemulihan dan saat sudah tidak mendapat PMT Pemulihan (p=0,430).Kesimpulan: Tidak ada perbedaan pada status gizi balita dengan indeks antropometri BB/TB saat sebelum PMT Pemulihan dan setelah PMT Pemulihan.